PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN JERUK LOKAL DAN IMPOR DI KOTA TASIKMALAYA - Karina, Dhea; Sundari, Ristina Siti; Hidayati, Reny (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2021)
Fruit commodity has high market demand and has economic value. One of them is a citrus fruit which has an excellent possibility to develop. Availability, continuity, and quantity of quality local fruit produced are still limited. Citrus encourages the entry of imported fruit in large quantities and of relatively good quality. The purpose of this study was to determine and analyze consumer preferences and behavior towards purchasing decisions of local oranges and imported citrus fruits in Tasikmalaya City and the attributes most considered by consumers in purchasing decisions for local oranges and imported citrus fruits in Tasikmalaya city. The quantitative research method was used on 90 respondents of local and imported citrus fruit consumers. The following analysis tools used in this study were multivariate analysis, Fishbein, and conjoin. Based on multivariate analysis results, it is known that Simultaneously and Partially Consumer Behavior influences the Purchase Decision on Local Citrus Fruits and Imported Oranges in Tasikmalaya. Based on the multi-attribute analysis of local oranges and imported oranges in Tasikmalaya, it is known that the value of consumer attitudes towards the attributes of imported citrus fruits is higher than local oranges, in addition, the results of the conjoint analysis, it is known that the most critical attributes according to consumers are different for local and imported oranges. Local oranges' attributes are considered essential regarding the trader's taste, peel color, price, aroma, and textureKomoditas buah-buahan memiliki permintaan pasar yang tinggi dan bernilai ekonomis. Salah satunya adalah buah jeruk yang memiliki kemungkinan menguntungkan untuk dikembangkan. Ketersediaan, kualitas, kuantitas, kontinyuitas buah lokal yang dihasilkan belum dapat memenuhi kebutuhan penduduk yang terus meningkat. Sehingga pemenuhannya dengan mengimpor buah jeruk dari luar. Maka dilakukan penelitian untuk menganalisis perilaku konsumen dalam pengambilan keputusan membeli buah jeruk impor dan buah jeruk lokal di Kota Tasikmalaya, dan atribut yang paling dipertimbangkan konsumen dalam pengambilan keputusan untuk membeli buah jeruk lokal dan buah jeruk impor di kota Tasikmalaya. Metode penelitian kuantitatif terhadap konsumen buah jeruk lokal dan konsumen buah jeruk impor sebanyak 90 responden. Penelitian ini menggunakan analisis multivariat dan, Fishbein. Hasil analisis menunjukkan secara simultan dan parsial perilaku konsumen dapat mempengaruhi keputusan dalam membeli buah jeruk di Tasikmalaya. Sikap konsumen terhadap atribut buah jeruk lokal lebih rendah daripada buah jeruk impor. Bagi konsumen atribut rasa, warna kulit, harga, aroma, tekstur pada jeruk lokal merupakan hal sangat penting yang perlu diperhatikan oleh penjual.